Antibacterial Activities of 3,5-Diaryl-4-Benzoyl-1-Pyridoyl-D2-Pyrazolines - Kadu, M.V.; Jamode, V.S.; Tambekar, D.H. (Asian Journal of Chemistry, 2012)
3,5-Diaryl-4-benzoyl-1-priydoyl-D2-pyrazolines have been synthesized from 3-aroyl flavanones and isoniazide in pyridine medium. Structures of these compounds have been characterized by spectral analysis. These compounds were tested for their antibacterial activities against pathogenic bacteria and are found to have remarkable activity.